2016
DOI: 10.1038/bjc.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a newly identified MALAT1 alternatively spliced transcript in breast cancer

Abstract: Background: Epigenetic deregulation is considered as a new hallmark of cancer. The long non-coding RNA MALAT1 has been implicated in several cancers; however, its role in breast cancer is still little known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…Its superior level in TNBC than in ER positive breast subtype, indicates that MALAT1 is more highly expressed in ER positive cell lines [47]. This ER-related expression has been supported both in full-length MALAT1 and an alternatively spliced variant of MALAT1 [48, 49]. By interacting with polycomb 2 protein, MALAT1 could mediate gene activation by relocating growth-related genes as well [50].…”
Section: Malat1mentioning
confidence: 99%
“…Its superior level in TNBC than in ER positive breast subtype, indicates that MALAT1 is more highly expressed in ER positive cell lines [47]. This ER-related expression has been supported both in full-length MALAT1 and an alternatively spliced variant of MALAT1 [48, 49]. By interacting with polycomb 2 protein, MALAT1 could mediate gene activation by relocating growth-related genes as well [50].…”
Section: Malat1mentioning
confidence: 99%
“…UCA1 upregulation and subsequent mTOR activation by UCA1 downregulates tumor‐suppressive miR‐143, which is stated as a potential mechanism (Tuo, Li, & Luo, 2015; Xue, Chen, & Li, 2016). GAS5 functions as a molecular sponge for miR‐21 that leads to increased PTEN expression, which in turn, brings about cell proliferation inhibition and apoptosis (Meseure et al, 2016). Li et al demonstrated that activation of mTOR/Akt signaling blocks GAS5 and attenuates the expression of PTEN, which advocates cancer cell growth and migration.…”
Section: Crosstalk Between Various Signaling Pathways and Lncrnasmentioning
confidence: 99%
“…Many cancer-related genes have been well characterized for both their functions and aberrant expression or splicing in cancers. In a study using a peptidomics approach to search for novel transcript variants in clinical proteomics, Zhang et al identified novel alternative splicing isoform biomarkers of breast cancer [86]. In another report, Venables et al compared alternative splicing profiles of 600 cancer-associated genes between normal and breast cancer samples, and validated 41 alternative splicing events that significantly differed among these two groups of samples.…”
Section: Clinical Application Of Alternative Splicing In Cancer Thmentioning
confidence: 99%